Phenomenology Approach in the Development of Cyber-Physical Systems (CPS) National Defense - Halkis, Mhd; Haq, Muhammad Shiratul (Technium Social Sciences Journal, 2021)
Applications in information systems connect between human interest and computer technology. Not all human activities can be fully transferred into information technology systems, but application methodologies need to be developed continuously. Command, Control, Communication, Computer, Intelligent, Surveillance, and Reconnaissance (C4ICR) as Cyber-Physical Systems (CPS) National Defense is a demand to be developed in the Industrial 4.0 era. To make essential innovations an appropriate and relevant methodology in order to get optimum product results. This study seeks to combine the Symbolic Interactionism (SI) methodology with the Rapid Application Development (RAD) methodology abbreviated as SIRAD. The steps in combining these methodologies are using the Husserlian Phenomenology paradigm. The SI methodology explains each human or group of people’s unique emotional and ethical values to be put together. The RAD methodology can assemble steps from modeling to implementation. After conducting experiments at the Military Commander and Force Headquarters, it can be concluded that information technology generation industry 4.0 can build C4ICR National Defense. However, in practice, human factors as users cannot necessarily be put together in a shared system permanently due to organizational and management traditions. For this reason, in building the C4ICR, it is essential to include the stages of building strong and dynamic regulations that are interoperability.